Spherical Dome Buckling With Edge Ring Support. (November 2016) - Rotter, J. Michael; Mackenzie, Greig; Lee, Martin
Abstract: Spherical dome roofs are widely used on large diameter tanks and silos, as they provide high strength for very limited amounts of material: buckling normally controls the design. Their design is currently based on very simple rules that were devised many decades ago. In particular, existing design is based on very simple boundary condition assumptions that cannot be realised in practice. This paper presents the first thorough study of the influence of realistic boundary conditions, in the form of a ring at the eaves, on the linear bifurcation of these domes. The outcome is a clear documentation of one of the key reference resistances required for a design description in the terminology of the Eurocode on shell buckling EN 1993-1-6. The complete study explored a very wide range of parameters, so only a sample of the findings is presented here. The complete results are expected to form the basis of future rules in the ECCS Recommendations on Buckling of Shells.